The impact of atypical sensory processing on adaptive functioning within and beyond autism: The role of familial factors. (November 2021) - Neufeld, Janina; Hederos Eriksson, Lisa; Hammarsten, Richard; Lundin Remnélius, Karl; Tillmann, Julian; Isaksson, Johan; Bölte, Sven
Atypical sensory processing is prevalent across neurodevelopmental conditions and a key diagnostic criterion of autism spectrum disorder. It may have cascading effects on the development of adaptive functions. However, its unique contribution to adaptive functioning and the genetic/environmental influences on this link are unclear. In a clinically enriched twin sample ( n = 289, 60 diagnosed with autism spectrum disorder), we investigated the associations between the quadrants of the Adult/Adolescent Sensory Profile (low registration, sensory sensitivity, sensation seeking, and sensation avoiding) and adaptive functioning. Associations were modeled across the cohort accounting for the effects of clinical diagnosis, IQ, sex and age, and within-twin pairs, additionally implicitly adjusting for familial factors. Furthermore, we explored interaction effects between atypical sensory processing and autism spectrum disorder diagnosis. Sensory sensitivity and sensation avoiding were associated with reduced adaptive functioning across individuals, but not within-twin pairs. An interaction effect was found between sensation seeking and autism spectrum disorder diagnosis, showing a negative association between sensation seeking and adaptive functioning only in individuals diagnosed with autism spectrum disorder. The results suggest that atypical sensory processing is associated with reduced adaptive functioning and that familial factors influence this link. In addition, sensation seeking behaviors might interfere with adaptive functioning specifically in individuals with autism spectrum disorder. Lay abstract: Individuals diagnosed with autism tend to process sensory information differently than individuals without autism, resulting for instance in increased sensitivity to sounds or smells. This leads to challenges in everyday life and may restrict the individual's daily functioning. How direct this link is, however, is currently unclear. We investigated this question in 289 twins of whom 60 were diagnosed with autism and further 61 were diagnosed with other neurodevelopmental disorders. We looked at the association between unusual sensory processing and adaptive skills, both across individuals and within-twin pairs, testing whether individuals with higher levels of atypical sensory processing showed reduced adaptive skills compared to their twins. Since twins share 50%–100% of their genes and part of their environment (e.g. family background), associations within-twin pairs are free from effects of these familial factors. We found that an increased sensitivity to, as well as the avoiding of, sensory input (hyper-responsiveness) was linked to reduced adaptive skills across individuals—but not within-twin pairs. We also found an association between the degree to which individuals seek for sensory input (sensation seeking) and reduced adaptive skills, but only in individuals diagnosed with autism. The results suggest that sensory hyper-responsiveness has negative effects on individuals' general ability to function, but that this link is influenced by familial factors and hence not direct. In addition, sensation seeking behaviors might have a negative impact on adaptive skills specifically in autistic individuals.